Analisis Tingkat Kesukaran Dan Daya Pembeda Pada Butir Soal Pilihan Ganda Mata Pelajaran Bahasa Indonesia Kelas V Semester 1 SDN Kedungdalem 2 - Ryzca Siti Qomariyah; Rr. Ghina Ayu Putri T.K; Dita Refani Putri; Desvita Sania Putri; Mohammad Reza Triya P (Jurnal Pendidikan, Sains Dan Teknologi, 2022)
This study aims to analyze the level of difficulty and power of difference in multiple choice items in order to determine the weight of each item so as to determine the level of students' understanding of learning. This research was conducted on October 25-29 2022. This analysis uses multiple choice item variables because it is easier to accommodate all learning material and easier to collect score calculations on student tests. This study uses a quantitative method whose writing uses aspect measurements, calculation formulas and certainty of numerical data. We collect data through students' answers to Indonesian language exam questions and then process the data by calculating the formula so that we get raw scores from the multiple choice questions. The results of this study indicate that the level of difficulty of the multiple choice questions at SD Negeri Kedungdalem 2 is still not good enough and needs improvement in the preparation of the questions.